Level of efficiency in using rice production inputs in Rainfed Land, Ulak Jeremun Village, Ogan Komering Ilir Regency - Muhammad Yamin; Siti Ramadani Andelia; Meitry Firdha Tafarini (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
High productivity was influenced by optimum production input. Efforts to optimize rice production results include examining the effectiveness of factors that influence rice productivity. This research was useful for providing levels of effective and efficient use of inputs to create efficient use of inputs in rice farming. The research aimed to analyze factors that influence rice productivity, analyze the efficiency of using production inputs in rice farming, and calculate rice farming income. This research was conducted in Ulak Jeremun Village, SP Padang District, Ogan Komering Ilir Regency. The location selection was carried out purposively or deliberately due to the reduction in planting area. Data collection was carried out from August to September 2023. The research method used in this research was the Survey Method. The sampling method used was a simple random sampling method with a total of 60 farmers as respondents. The data used in this research consists of primary data and secondary data. The results of the research show that (1) Factors that have a significant influence on rice productivity in Ulak Jeremun Village are land area, urea fertilizer, and TSP fertilizer. In contrast, those that do not have a significant influence are the dosage of phonska, pesticides, herbicides, fungicides, and the number of workers. (2) The efficiency of production inputs in terms of price for the dose used for seeds and the number of workers was efficient. In contrast, the dose used for fertilizers, insecticides, and pesticides could be more efficient. (3) Rice farming income in Ulak Jeremun Village was IDR 6,940,251 per hectare per year. Income was relatively small because farmers' land was flooded, so many weeds, which cause pests in the fields, were difficult for farmers to control.